SUPERVISION FUNCTION URGENCY OF CORRUPTION CRIMINAL PREVENTION MEASURES IN BANTAENG DISTRICT - Mulyati Pawennei; A. Rahim; Tahiruddin Tahiruddin (International Peneliti Ekonomi, Sosial dan Teknologi, 2019)
This study aims to determine the supervision system carried out by the local government of Bantaeng Regency as an effort to prevent corruption in Bantaeng district and to find out the legal basis that underlies the birth of the surveillance system carried out by the Bantaeng district government. The results of this study indicate that the supervision system in the effort to prevent criminal acts of corruption in Bantaeng district is less effective because there are still indications of budget misuse that result in corruption. Based on available data, it is necessary to develop a more effective system in terms of preventing the occurrence of criminal acts of corruption in Bantaeng district by conducting supervision attached to each of the existing agencies, to prevent earlier irregularities that cause corruption in Bantaeng district.